Pelatihan Pembuatan Produk Permen Jelly Berbahan Dasar Pisang Di Desa Pakuan - Zainuri; Amuddin; Pertiwi, Made Gendis Putri; Sari, Ira Musfita; Cicilia, Siska; Utama, Qabul Dinanta; Nofrida, Rini; Amaro, Moegiratul; Ariyana, Mutia Devi; Pawestri, Setyaning; Handayani, Baiq Rien; Saputra, Oki (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Pakuan Village is one of the villages in Narmada Sub-district, West Lombok Regency where banana production is very abundant but has not been maximally utilized by the vilagers. Generally, bananas are only sold fresh or banana chips and banana sale. Bananas have the potential to become raw materials for various food products. The limited knowledge of the villagers regarding banana processing technology causes a lack of innovation in producing processed banana products. The purpose of this service activity is to increase villagers knowledge related to banana processing technology to support the strengthening of the capacity of MSMEs in Pakuan Village. This activity involved around 12 MSMEs groups. Activities were carried out in 3 stages, namely preliminary studies, socialization and training, and evaluation. The approach method used was a participatory approach. Through this activity, the villagers succeeded in increasing the knowledge and skills needed in processing bananas into jelly candy and fostering community interest in innovating to develop other food products made from bananas. The diversification of banana products can be one way to improve the economy and welfare of the community.